Reducing Inefficiency in the Pharmaceutical Industry: a Case Study of Lean Manufacturing Implementation in a Pharmaceutical Industry - Hardiansyah Sucipta; Ratih Dyah Kusumastuti (Eduvest - Journal of Universal Studies, 2025)
The pharmaceutical industry in Indonesia has grown significantly, accounting for 27.8% of the ASEAN market share. However, despite this growth, the sector faces challenges, including intense competition, complex supply chain dynamics, and inefficiencies in production processes. This research investigates the factors contributing to the production decline and identifies non-value-added activities in the Vitamin C production line using Value Stream Mapping. The study applies Lean Manufacturing principles, supported by Root Cause Analysis, to propose improvement strategies that enhance line utilization and reduce waste. Data were collected through observation and interviews leading to the development of current and future state process models. The findings reveal that ineffective scheduling, prolonged changeover times, and labour-intensive documentation significantly reduce production efficiency. To address these issues, the study recommends the implementation of rapid testing technologies, electronic batch records, and a Laboratory Information Management System. These interventions are expected to result a 62.7% reduction in lead time and a 176% increase in production capacity. Financial analysis indicates strong economic feasibility, with a positive net present value and short payback period. This study concludes that Lean Manufacturing tools, when tailored to pharmaceutical operations, can drive substantial improvements in productivity, process flow, and operational resilience.